The Association of Salivary Serotonin With Mood and Cardio-Autonomic Function: A Preliminary Report - Karbownik, Michał Seweryn; Hicks, Steven Daniel (Frontiers in Psychiatry, 2022)
Background. Serotonin plays an important role in mood regulation and depression. However, it is not clear whether the levels of serotonin in saliva are related to current mood. Aim. To test the association of salivary serotonin concentrations with mood, as well as cardiovascular and autonomic parameters. Materials and Methods. Saliva samples were obtained from collegiate runners and output parameters were examined before and after physical activity. Results. Salivary serotonin concentration was negatively associated with current mood (β = -0.32, 95%CI -0.62 to -0.02, p = 0.037, analysis adjusted for potential confounders), but insignificantly with measured cardiovascular and autonomic parameters. Conclusions. Salivary serotonin may reflect current mood. The results are preliminary and require further evaluation.